2022
DOI: 10.3390/s22134789
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model for Predicting Sit-to-Stand Trajectories of People with and without Stroke: Towards Adaptive Robotic Assistance

Abstract: Sit-to-stand and stand-to-sit transfers are fundamental daily motions that enable all other types of ambulation and gait. However, the ability to perform these motions can be severely impaired by different factors, such as the occurrence of a stroke, limiting the ability to engage in other daily activities. This study presents the recording and analysis of a comprehensive database of full body biomechanics and force data captured during sit-to-stand-to-sit movements in subjects who have and have not experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To address home-based rehabilitation programs, a variety of systems have been designed with different technologies such as vision including depth and RGB cameras, 26 – 49 and wearables, such as Inertial Measurement Units (IMU). 50 69 Some systems also used pressure-sensing technologies, such as pressure sensitive mats (with electronic textiles) and insole pressure sensors, 70 81 to measure the pressure of body limbs and its distribution on the respective areas. In each subsection, we begin with the outcomes of studies that performed joint angle measurement or estimation, followed by the studies that performed exercise recognition and/or exercise quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address home-based rehabilitation programs, a variety of systems have been designed with different technologies such as vision including depth and RGB cameras, 26 – 49 and wearables, such as Inertial Measurement Units (IMU). 50 69 Some systems also used pressure-sensing technologies, such as pressure sensitive mats (with electronic textiles) and insole pressure sensors, 70 81 to measure the pressure of body limbs and its distribution on the respective areas. In each subsection, we begin with the outcomes of studies that performed joint angle measurement or estimation, followed by the studies that performed exercise recognition and/or exercise quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the previous approaches, the reviewed studies either estimated joint angles, or gait parameters 71 , 75 , 79 or used ML for activity recognition. 70 , 73 , 74 , 76 , 77 , 80 , 81 However, it is worth noting that there is still a noticeable lack of work in the area of exercise assessment modules using this technology, as only one study was identified and categorized within this domain. 72 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation